Pengukuran Tebal Kontaminasi Zat Radioaktif pada Permukaan Tanah Secara In Situ Menggunakan Spektrometer Gamma Portabel - Wijianto Wijianto; Much. Azam; Evi Setiawati; Bunawas Bunawas (BERKALA FISIKA, 2012)
Determination of contamination’s thickness on the ground for homogeneous source compound Cs -137 and Co-60 use portable gamma spectrometry with height purity germanium detector ( HPGe detector) have been done.There are two methods to determine contamination’s thickness on the ground surface. The first method is Korun’s modification by looking for the total count of gamma ray before and already to experience attenuation for Cs-137 and Co-60 then divided by the decrease of linear attenuation coefficient Cs-137 and Co-60. The second is Xu comparison method by made variation of distance from ground surface to detector surface then compared with total count of gamma ray from one source Cs-137 or Co-60 during counting time. The results from experiment obtained for Korun’s modification for the actual thickness 10 cm, 20 cm and 24 cm have an error at 2 % , for actual thickness 12 and 16 cm,and an error at 3 %, for actual thickness 6 cm and 8 cm an error of 4 % and, for actual thickness 4 cm have an error at 9 %. Then for the Al Ghamdi to Xu Comparison method, for Co-60 in the actual thickness 6 cm and 10 cm have error 3 % and 12 %, and for Cs-137 in the actual thickness 10 cm and 6 cm have error 9 % and 48 %. Key words: HPGe detector, portable gamma spectrometry, contamination, Korun’s modification and Xu comparison method.